Local therapy combined with chemotherapy versus chemotherapy for postoperative oligometastatic non-small-cell lung cancer. (11th March 2019) - Shang, Shuheng; Wang, Linlin; Su, Yi; Li, Butuo; Guo, Meiying; Zhu, Zhaofeng; Sun, Xindong; Yu, Jinming
Aim: To compare the efficacy and toxicity of local therapy plus chemotherapy versus chemotherapy in non-small-cell lung cancer (NSCLC) patients with oligometastases after surgery.Patients & methods: A total of 152 patients with oligometastases after surgery were enrolled. Data of patient survival, treatment response and toxicities were compared between the groups receiving local ablative therapy plus chemotherapy and chemotherapy alone.Results: Compared with chemotherapy, the combination treatment conferred better progression-free survival, objective response rate and disease control rate (10 vs 7 months; 66.7 vs 31.9%; 94.3 vs 80.9%, respectively), but with more grade ≥3 adverse events. Besides, the overall survival was not significantly different (19 vs 20 months).Conclusion: The addition of local therapy to chemotherapy improved progression-free survival, objective response rate and disease control rate, but not overall survival in postoperative oligometastatic non-small-cell lung cancer.